Pengembangan Aplikasi Pelaporan Jalan Rusak Di Kelurahan Bulupabbulu Kecamatan Tempe Kabupaten Wajo Berbasis Android - Iskandar, Nurul Fadhil; Zulhajji; Fathahillah (Jurusan Teknik Informatika dan Komputer, 2023)
This study aims to determine the results of developing the Android-based Application for Damaged Road Reporting in Bulupabbulu Village, Tempe District, Wajo Regency based on the results of ISO 25010 testing standards and to determine the results of using the Damaged Road Reporting Application in Bulupabbulu Village, Tempe District, Wajo Regency based on Android. The development model used is a prototype and application quality testing based on the ISO 25010 quality standard. Based on the test results using the ISO 25010 quality standard, the damaged road reporting application has met the standards where: a) the percentage of eligibility is 100% in the Very Good category and has fulfilled the functionality aspect suitability; b) results of 100% are obtained and are in the very good category and have fulfilled the compatibility aspect; c) testing the performance efficiency aspect of the application can run properly without experiencing a memory leak resulting in force close and launch fail; d) the results obtained by 100% of users assess the developed application to be in the Very Good category and have fulfilled the usability aspect.